2016
DOI: 10.3109/10826084.2015.1110174
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of Social Anxiety in Marijuana and Cigarette Use Motives Among Adolescents

Abstract: Marijuana and nicotine are two of the most widely used substances among adolescents in the United States. Symptoms of social anxiety (SA) typically emerge during early adolescence, and elevated levels are associated with increased substance-related problems despite inconsistent links to frequency of use. Substance use motives, and in particular coping motives, have been found to play an important role in understanding the heightened risk for use problems among those with elevated SA. Importantly, work to date … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 65 publications
0
15
0
Order By: Relevance
“…While the classes differed on many of the selected variables at the descriptive level (see Table 1), in the final models with all of the variables entered simultaneously, classes that should have differed on more variables (e.g., Low Motives and High Motives) were statistically similar. In addition to collecting larger samples, future work should consider other important risk factors, such as social anxiety (Cloutier et al, 2016), distress tolerance (Semcho et al, 2016), trauma exposure/post-traumatic symptom severity (Bonn-Miller, Vujanovic, Feldner, Bernstein, & Zvolensky, 2007), and externalizing symptoms (Hussong, Ennett, Cox, & Haroon, 2017) as well as protective factors, such as protective behavioral strategies (Pederson et al, 2016) and healthy emotional self-regulation (Dvorak & Day, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the classes differed on many of the selected variables at the descriptive level (see Table 1), in the final models with all of the variables entered simultaneously, classes that should have differed on more variables (e.g., Low Motives and High Motives) were statistically similar. In addition to collecting larger samples, future work should consider other important risk factors, such as social anxiety (Cloutier et al, 2016), distress tolerance (Semcho et al, 2016), trauma exposure/post-traumatic symptom severity (Bonn-Miller, Vujanovic, Feldner, Bernstein, & Zvolensky, 2007), and externalizing symptoms (Hussong, Ennett, Cox, & Haroon, 2017) as well as protective factors, such as protective behavioral strategies (Pederson et al, 2016) and healthy emotional self-regulation (Dvorak & Day, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…To date, the majority of the motives research has used variable-centered analysis (e.g., linear/multiple regression), which examine relationships among variables (e.g., to predict outcomes; Muthén & Muthén, 2000). This is a concerning limitation of the literature given the high correlations often found across substance use motives, including marijuana (Kuntsche et al, 2005;Simons et al, 1998), which are typically handled by examining motives in isolation (e.g., Bonn-Miller, Vujanovic, & Zvolensky, 2008) or by statistically controlling for other motives (e.g., Cloutier, Blumenthal, & Mischel, 2016;Semcho, Bilsky, Lewis, & Leen-Feldner, 2016). However, these approaches assume that participants have been sampled from a single population (Collins & Lanza, 2010), ignoring unobserved heterogeneity that may exist within populations, and therefore cannot examine how the heterogeneity in marijuana motive profiles may differentially relate to distinct marijuanarelated outcomes.…”
Section: Marijuana Motives and Person-centered Analysismentioning
confidence: 99%
“…Bayani reported that students with higher levels of social phobia have poor problemsolving ability and greater depression (20). It has also been shown that social phobia is correlated with adjustment problems (21), intolerance of ambiguities (22), mood disorders (23), increase in cigarette and marijuana use (24), social isolation (25), QOL (26), avoidant personality (27,28), and bipolar disorder (29). Personality and psychopathology are two categories of the field of psychology, which have gained the interest of many researchers.…”
Section: Introductionmentioning
confidence: 99%
“…None of the 17 studies identified significant associations between anxiety and cannabis use. Specifically, anxiety and social anxiety were not significantly associated with use [68][69][70][71][72][73][74][75][76][77][78], use frequency [79][80][81], problems [69,74,82], or coping motives [69,83]. Unclear findings also occurred, such as an association appearing in one model of a study, but losing significance as additional variables were added to later models [84].…”
Section: Primary Outcomesmentioning
confidence: 94%